Effect of planting dates on the yield of broccoli genotypes (Bangladesh Journal of Agricultural Research, 2015)
This experiment was conducted during September, 2011 to March, 2012 in the experimental field of Department of Horticulture, Bangabandhu Sheikh Mujibur Rahman Agricultural University (BSMRAU), Gazipur to find out the effect of planting date on the yield of broccoli genotypes. There were five genotypes viz. Early green, Forest green, Green calabrese, Premium crop and Green king and four planting dates viz. 2 October, 27 October, 21 November and 16 December. The treatment effects were statistically analyzed and found significant in most of the characters studied. Genotype Green calabrese was the highest in average plant height (53.70 cm). Green king produced the maximum spread diameter (69.23 cm), stem diameter (30.35 mm) and early initiation of floral head. Genotype Early green performed the best regarding head weight (343.87 g), yield per plant (477.4 g) and yield (19.10 t/ha). Broccoli planted on 21 November initiated early flower head, maximum head diameter (16.99 cm), head weight (314.49 g), yield per plant (453.64 g) and total yield (18.15 t/ha). The genotype Early green planted on 21 November showed the best performance in yield per plant (580.17 g) and yield hectare (23.21 t/ha).Bangladesh J. Agril. Res. 40(3): 465-478, September 2015